Exporting essentials : selling products and services to the world successfully - Delaney, Laurel J. (Apress, 2014)
Exporting Essentials: Selling Products and Services to the World Successfully is for entrepreneurs and small business owners?the makers, movers, and shakers in our world?interested in taking their businesses to the next level of growth through exports. This short, hard-hitting book covers just the essentials, providing the tools you need to tap new markets. And it couldn't be more timely. In the old days, creating an international business was left to relatively few--those with the wherewithal to move boatloads of goods into foreign countries. But now, thanks to the Internet, businesses of all sizes have a huge new opportunity to sell both goods and services globally. Yet only 1% of all U.S. businesses export. Why? Typically, exporting begins with unsolicited inquiries from foreign customers on the web via email, website, blog, or posting on a Facebook page. People outside your country want your product, and they want it now. The problem is that most small business owners do not know how to service these inquiries. What's the best way to ship goods? Do I need a license? Should I sell through wholesalers in specific countries or directly to consumers? How will I get paid? Help is here?Exporting Essentials, an abridged version of the author's Exporting: The Definitive Guide to Selling Abroad Profitably, equips you with the knowledge you need to sell and fulfill orders internationally. It also imparts a can-do spirit on exporting, leading to greater revenues, stability, and profitability for your business. Exporting Essentials: Selling Products and Services to the World Successfully: Lays out simple steps to conduct market research, find customers, open new markets, get paid, and ship goods and services. Shows you how to adapt your product or service for export. Provides insider tips and strategies to export efficiently and profitably. Explains how the U.S. government helps exporters. With 70 percent of global buying power lying outside U.S. borders, exporting is not just an option for ambitious entrepreneurs?it?s an absolute must for building and sustaining a successful future.